2003
DOI: 10.1093/molehr/gag029
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin, activin, follistatin, activin receptors and beta-glycan gene expression in the placental tissue of patients with pre-eclampsia

Abstract: The objective of this study was to quantify the relative expression of inhibin alpha, inhibin/activin beta(A), beta(B), beta(C), follistatin, activin receptors and beta-glycan genes in placental tissue of term pre-eclamptic patients and controls to investigate if these genes are up-regulated in the placenta in pre-eclampsia. Seven women with pre-eclampsia symptoms were matched with 10 normal pregnant controls for gestational age, maternal age, and parity. Total RNA was isolated from each sample. Complementary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 38 publications
1
30
0
1
Order By: Relevance
“…Recently, levels of activin A and inhibin A were demonstrated to be significantly elevated in the blood circulation of women who have developed preeclampsia (Bersinger et al 2002;Muttukrishna et al 1997Muttukrishna et al , 2000. The expression of inhibin-a subunit, b A , b B and b C subunits, follistatin, betaglycan and activin receptor genes were demonstrated in placental tissue from both uncomplicated term pregnancies and term pregnancies with preeclampsia (Casagrandi et al 2003), supporting the results of elevated of inhibin A and activin A levels in maternal serum (Muttukrishna et al 2000) and placental homogenates (Bersinger et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, levels of activin A and inhibin A were demonstrated to be significantly elevated in the blood circulation of women who have developed preeclampsia (Bersinger et al 2002;Muttukrishna et al 1997Muttukrishna et al , 2000. The expression of inhibin-a subunit, b A , b B and b C subunits, follistatin, betaglycan and activin receptor genes were demonstrated in placental tissue from both uncomplicated term pregnancies and term pregnancies with preeclampsia (Casagrandi et al 2003), supporting the results of elevated of inhibin A and activin A levels in maternal serum (Muttukrishna et al 2000) and placental homogenates (Bersinger et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, this subunit has been detected in cells from several other organs, including normal or malignant prostate and ovarian, testicular, endometrial, and pituitary tissues (Loveland et al 1996;Mellor et al 2000;Gold et al 2004Gold et al ,2009Kimmich et al in press). The inhibin bC gene was detected in placental tissue from uncomplicated term pregnancies and pregnancies with preeclampsia (Casagrandi et al 2003). We have demonstrated the presence of the inhibin bC subunit at the transcriptional level and at the protein level in the normal human placenta.…”
Section: Discussionmentioning
confidence: 67%
“…31,32 Furthermore, in a cross-sectional cohort study, Keelan et al 33 showed that serum levels of FST are increased in preeclamptic women compared to normotensive pregnant women. In contrast, Casagrandi et al 34 demonstrated that placental FST expression does not differ between preeclamptic women and normotensive pregnant women. The present longitudinal study demonstrates, for the first time, that serum FST significantly declines in preeclamptic women compared with normotensive pregnant women.…”
Section: Discussionmentioning
confidence: 87%